2018
DOI: 10.1111/tid.12980
|View full text |Cite
|
Sign up to set email alerts
|

Fosfomycin trometamol in the prophylaxis of post‐kidney transplant urinary tract infection: A controlled, randomized clinical trial

Abstract: The addition of FOS to TMP-SMX was not beneficial for the prevention of UTI after RT in our setting. (ClinicalTrials.gov, NCT01820897).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…This was an important study that compared the efficacy of FOS 3 g every 10 days (in addition to TMP-SMX) administered during the first 6 months to KTR (n = 32) vs standard TMP-SMX prophylaxis (n = 35) and found no difference in the incidence of UTI (41 vs 43%) or the median time to UTI (7 days). 1 Although in their study, that included recipients of both living and deceased donors, FOS was not beneficial for the overall prevention of UTI, there was reduced number of patients with UTI due to Escherichia coli and Enterococcus faecalis in the FOS-treated group. 1 Previous reports have shown efficacy of FOS for patients undergoing urological procedures and in females with recurrent UTI.…”
Section: Efficacy and Tolerability Of Fosfomycin In Prevention Of Recmentioning
confidence: 92%
See 2 more Smart Citations
“…This was an important study that compared the efficacy of FOS 3 g every 10 days (in addition to TMP-SMX) administered during the first 6 months to KTR (n = 32) vs standard TMP-SMX prophylaxis (n = 35) and found no difference in the incidence of UTI (41 vs 43%) or the median time to UTI (7 days). 1 Although in their study, that included recipients of both living and deceased donors, FOS was not beneficial for the overall prevention of UTI, there was reduced number of patients with UTI due to Escherichia coli and Enterococcus faecalis in the FOS-treated group. 1 Previous reports have shown efficacy of FOS for patients undergoing urological procedures and in females with recurrent UTI.…”
Section: Efficacy and Tolerability Of Fosfomycin In Prevention Of Recmentioning
confidence: 92%
“…1 Although in their study, that included recipients of both living and deceased donors, FOS was not beneficial for the overall prevention of UTI, there was reduced number of patients with UTI due to Escherichia coli and Enterococcus faecalis in the FOS-treated group. 1 Previous reports have shown efficacy of FOS for patients undergoing urological procedures and in females with recurrent UTI. [2][3][4][5] Clinical cure rates were 67% for lower-UTI and 80% for upper-UTI in a study that included 40 KTR.…”
Section: Efficacy and Tolerability Of Fosfomycin In Prevention Of Recmentioning
confidence: 92%
See 1 more Smart Citation
“…The tromethamine is a proton acceptor used to stabilize the oral formulation of fosfomycin [ 8 ]. We recently conducted a randomized controlled trial at our hospital that showed the efficacy of fosfomycin for prophylaxis of urinary tract infections after kidney transplantations [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,5 However, clinical data supporting the use of FOS in aSOT are limited. 3,[6][7][8] The aim of this study was to evaluate the use of FOS for the treatment of cystitis retrospectively in the aSOT population at both the FDA-approved single-dose regimen and the off-label multidose regimens.…”
mentioning
confidence: 99%